Blood Lead Level Among Paediatric Thalassaemia Patients In Kota Bharu, Kelantan - Mohd Igbal@ Mohd Iqbal, M.Iyen (2011)
Lead toxicity has been recognized for thousands of years. Today, lead toxicity is well documented and is recognized as a major environmental health risk throughout the world. Lead affects humans and animals of all ages, but the effects of lead are most serious in young children. The route of lead exposure is primarily via inhalation or ingestion. However Bearer et al has shown that blood transfusion can be a source for lead exposure to premature infants. Thalassemia is common in this country, and majority of patients are transfusion dependant, thus hypothesis been made that regular blood transfusion can represent a significant source of lead in our Thalassaemic patients. To determine Blood Lead Level in Thalassaemic patients with regular blood transfusion and to compare means with non-Thalassaemic patients. This was a cross sectional study, conducted at the Paediatric Thalassaemia Day Care Unit, General Paediatric Ward (Ward 6 Selatan) and Paediatric Clinic in Hospital Universiti Sains Malaysia (HUSM) from March 2009 until August 2010. A total of 90 patients were included, 45 were Thalassaemic transfusion dependant patients and the other 45 were control who were of same age and sex with patients group and never been transfused before. The blood lead samples were taken pretransfusion for Thalassaemic patients group and random for control group. Samples were then analysed using standard Atomic Absorption Spectrometer analysis. This study revealed that overall mean blood lead level (2.13 ± 1.72J.Lg/dL) was low compared to standard CDC recommendations action plan levels. There was statistically significant difference between mean blood lead levels in Thalassaemic patients group (1.14 ± 0.85J.1g/dL) and control group (3.12 ± 1.8lJ.1g/dL). No correlations of age or serum ferritin level to blood lead level were found. This study shows that our Thalassaemic transfusion dependant patients do not have extra exposure to lead from their regular blood transfusion.